Determinants of Corporate Derivatives Usage for Hedging Purpose - Zeng, Shuzhuang (2005)
This paper provides empirical evidence on determinants of corporate derivatives usage by UK large-capitalisation corporations. In particular, the paper examines the corporate activities of derivative instruments usage for hedging purpose and tests theoretical hypotheses of hedging in risk management. Logit regression model is used to test whether the relationships between financial characteristics and the likelihood of using derivatives are consistent with the hedging hypotheses Ordinary Least Square (OLS) regression model is applied to investigate whether the connections between financial characteristics and the extent of currency derivatives support the hedging hypotheses. Data about corporate derivative activities are obtained from 2004 financial statements for 162 FTSE 250 Index firms. Out of the total sample of 162 companies, 127 companies report use of derivatives for the fiscal year 2004 and disclose information on derivative hedging activities; the remaining 35 companies report no use of derivatives for 2004. Based on evidence, the author draws the following conclusions in respect of the hypotheses of hedging: evidence is mixed with respect to financial distress costs hypothesis; evidence is consistent with hypotheses emphasizing the roles of agency costs arising from external financing, substitutes for hedging with derivatives, relevant risk exposure, and managerial risk aversion.